Build Positive Emotions During Pandemic Covid-19 - Muhammad Anwari (Borneo Community Development, 2021)
The whole world is facing a co-19 virus pandemic. Because the spread of covid-19 virus is very rapid, currently the government is implementing new normal to carry out daily activities to reduce the spread of covid-19 vius. However, people still tend to lack positive emotions in their daily activities. In this case the researcher used the study of literature research method, which explained from previous research. Can build positive emotions during the covid-19 pandemic virus and apply it in everyday life. By applying positive emotions during Padvid Covid-19 which will reduce the feeling of stress levels. Stress can result in a decrease in body immunity. If there is a decrease in the body's immune system will result in an outbreak of various viruses including covid-19 virus.